The significance of music in teaching Turkish - Göher Vural, Feyzan (The New Research of Tuva, 2018)
The whole history of teaching foreign languages is, in a way, a search for the best methodologies of doing so. Methods of teaching can be seen as systems providing the optimal ways of getting basic knowledge of a foreign language for students. The existing wide variety of methods suggests the choice of those most efficient for particular individuals. Each of the methodologies used relies on a number of theoretical underpinnings. This article advances proposals on using music in teaching Turkish as a foreign language, based on the principles of suggestopedia — the psychology of positive teaching developed by G. Lozanov. It is claimed that suggestopedia helps students learn a foreign language 3 to 5 times faster than those who rely on traditional methods of study.Suggestopedia makes colloquial dialogues in a foreign language be pronounced and/or listened to in the same way as music, and music is used as a facilitating and motivating factor, without lyrics. However, teaching based on suggestopedia alone will not suffice, since in the classical form it is limited by adult audiences and small ones to boot. Other peculiarities of students and groups also have to be accounted for, such as their linguistic background: if their first language is a Turkic one, they can be expected to learn Turkish faster, since they are already familiar with the melodic mode of the language.It can nevertheless be postulated that the use of songs in language learning helps develop such skills as vocabulary, rules of grammar and correct pronunciation. Songs facilitate teaching new words, grammatical rules, learning direction, layout, numbers and demonstrative adjectives. This is both useful and interesting for all categories of learners, children as well as adults.
Keywords: Turkish language; methods of teaching language; problems of teaching language; music; Turkey